Reliability of videotaped observational gait analysis in patients with orthopedic impairments - Jaap J. Brunnekreef; C.J.T. van Uden; Steven van Moorsel; Jan G.M. Kooloos (2005)
In clinical practice, visual gait observation is often used to determine gait disorders and to evaluate treatment. Several reliability studies on observational gait analysis have been described in the literature and generally showed moderate reliability. However, patients with orthopedic disorders have received little attention. The objective of this study is to determine the reliability levels of visual observation of gait in patients with orthopedic disorders.The gait of thirty patients referred to a physical therapist for gait treatment was videotaped. Ten raters, 4 experienced, 4 inexperienced and 2 experts, individually evaluated these videotaped gait patterns of the patients twice, by using a structured gait analysis form. Reliability levels were established by calculating the Intraclass Correlation Coefficient (ICC), using a two-way random design and based on absolute agreement.The inter-rater reliability among experienced raters (ICC = 0.42; 95%CI: 0.38-0.46) was comparable to that of the inexperienced raters (ICC = 0.40; 95%CI: 0.36-0.44). The expert raters reached a higher inter-rater reliability level (ICC = 0.54; 95%CI: 0.48-0.60). The average intra-rater reliability of the experienced raters was 0.63 (ICCs ranging from 0.57 to 0.70). The inexperienced raters reached an average intra-rater reliability of 0.57 (ICCs ranging from 0.52 to 0.62). The two expert raters attained ICC values of 0.70 and 0.74 respectively.Structured visual gait observation by use of a gait analysis form as described in this study was found to be moderately reliable. Clinical experience appears to increase the reliability of visual gait analysis.